Effect of hand sanitizer on the performance of fingermark detection techniques. (April 2017) - Chadwick, Scott; Neskoski, Melissa; Spindler, Xanthe; Lennard, Chris; Roux, Claude
Highlights: Investigation into the effect of hand sanitizer on fingermark detection techniques. Alcoholic hand sanitizers found to have no effect on common development techniques. Non-alcoholic hand sanitizers lead to an observable increase in development quality when using amino acid reagents. Increased development potentially due to the active ingredient in non-alcoholic hand sanitizers – benzalkonium chloride. Abstract: Hand sanitizers have seen a rapid increase in popularity amongst the general population and this increased use has led to the belief that hand sanitizers may have an effect on subsequent fingermark detection. Based on this hypothesis, three alcoholic and two non-alcoholic hand sanitizers were evaluated to determine the effect they had on the detection of fingermarks deposited after their use. The following fingermark detection methods were applied: 1, 2-indanedione-zinc, ninhydrin, physical developer (porous substrate); and cyanoacrylate, rhodamine 6G, magnetic powder (non-porous substrate). Comparison between hand sanitized fingermarks and non-hand sanitized fingermarks showed that the alcohol-based hand sanitizers did not result in any visible differences in fingermark quality. The non-alcoholic hand sanitizers, however, improved the quality of fingermarks developed with 1, 2-indanedione-zinc and ninhydrin, and marginally improved those developed with magnetic powder. Different parameters, including time since hand sanitizer application prior to fingermark deposition and age of deposited mark, were tested to determine the longevity of increased development quality. The non-alcoholic hand sanitized marks showed no decrease in quality when aged for up to two weeks. The time since sanitizer application was determined to be an important factor that affected the quality of non-alcoholic hand sanitized fingermarks. It was hypothesized that the active ingredient in non-alcoholic hand sanitizers, benzalkonium chloride, is responsible for the increase in fingermark development quality observed with amino acid reagents, while the increased moisture content present on the ridges resulted in better powdered fingermarks.